Peran Akreditasi Sekolah atau Madrasah dalam Meningkatkan Kualitas Pendidikan Indonesia - Koto, Eldawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This article discusses the efforts to ensure the quality of education in Indonesia through the school accreditation process. School accreditation is a comprehensive assessment of the eligibility of educational programs based on the National Education Standards (SNP) as a form of public accountability. Accreditation is carried out by comparing the school's conditions with the four components (standards) established in IASP 2020. In its implementation, the continuous fulfillment and development of these four components lead to the provision of quality education. Accreditation is an effort to accelerate and encourage the growth and development of schools/madrasahs, and motivate them to achieve the desired standards. This is expected to create a conducive environment for educational growth, provide guidance for continuous self-evaluation, and serve as a stimulus to continue striving for the expected quality. Thus, accreditation indirectly ensures the quality of education, which is beneficial for students, teachers, and the community in choosing schools for their children.